Carbon Fiber and Syntactic Foam Hybrid Materials via Core–Shell Material Extrusion Additive Manufacturing. Issue 12 (29th October 2020) - Pack, Robert C.; Romberg, Stian K.; Badran, Aly A.; Hmeidat, Nadim S.; Yount, Trenton; Compton, Brett G.
Abstract: Biological materials often employ hybrid architectures, such as the core–shell (C–S) motif present in porcupine quills and plant stems, to achieve unique specific properties and performance. Drawing inspiration from these natural materials, a new method to fabricate lightweight and stiff C–S architected filaments is reported. Specifically, a C–S printhead conducive to printing highly loaded fiber‐filled inks, as well as a new low‐density syntactic foam ink, are utilized to 3D‐print C–S architectures consisting of a syntactic epoxy foam core surrounded by a stiff carbon fiber‐reinforced epoxy composite shell. Effective printing of test specimens and structures with controlled geometry, composition, and architecture is demonstrated. The new foam ink exhibits density as low as 0.68 g cm −3 and C–S structures exhibit up to 25% higher specific flexural stiffness ( E 1/3 /ρ) than either constituent alone. Finally, a new mechanical model is presented to predict this performance improvement while accounting for potential eccentricity of the core. Abstract : For the first time, high performance core–shell (C–S) hybrid materials, composed of a low‐density syntactic foam core and stiff, carbon fiber‐reinforced shell, are printed via direct ink writing. 3D‐printed C–S architectures exhibit up to 25% higher specific flexural stiffness compared to constituent materials alone, showing benefit for use in weight sensitive applications.